The Role of the Social Media Platform Tiktok in Shaping Public Opinion on the Case of Teen Bullying in Cilacap Among Teenagers in Cirebon City and Regency - Defi Febrianti; Siti Khumayah; Farida Nurfalah (Ridwan Institute, 2026)
The rapid development of social media, particularly TikTok, has transformed the way adolescents access information and form public opinions. The viral teenage bullying case in Cilacap in 2023 illustrates how TikTok can influence adolescents’ perceptions of social issues. This research aims to examine the role of TikTok in shaping public opinion regarding the Cilacap bullying case among adolescents in Cirebon City and Cirebon Regency from the perspective of New Media Theory. A qualitative case study design was employed, involving eight adolescents aged 15–18 years who actively used TikTok and became aware of the case through the platform. Data were collected through semi-structured interviews and documentation, then analyzed using thematic analysis. The findings reveal that TikTok served as the primary source of information for adolescents in following the case. The interactive, participatory, and rapid characteristics of new media facilitated public opinion formation through audiovisual content, comment sections, repost features, and user engagement. The study identified differences in digital participation between adolescents from Cirebon City and Cirebon Regency, with participants from Cirebon City showing greater involvement in expressing opinions and sharing information, while participants from Cirebon Regency tended to engage more passively in discussions. Furthermore, exposure to the case increased adolescents’ awareness of digital literacy and highlighted the importance of verifying information before accepting or redistributing content. This study concludes that TikTok plays a significant role in shaping adolescent public opinion through interactivity, user participation, and rapid information dissemination. However, these advantages must be supported by adequate digital literacy to encourage critical evaluation of information and responsible social media use.